On the Mattering of Silence and Avowal: Joseph Beuys’ Plight and Negative Presentation in Post-1945 Visual Art - Ray, Gene (The Nordic Journal of Aesthetics, 2016)
Joseph Beuys’ installation Plight (1985) forcefully avows of the Nazi genocide by means of negative presentation. The work culminates a collective artistic investigation of negative sculptural strategies for representing traumatic history, opened by the Nouveaux Réalistes under the impact of Alain Resnais’ documentary film Nuit et Brouillard. This article outlines this history and analyzes Plight in the context of the ‘after Auschwitz’ crisis of representation and traditional culture theorized by Theodor W. Adorno. For Adorno, Auschwitz demonstrated threats to autonomous subjectivity posed by tendencies unfolding within the global social process of modernity itself. Reflecting on the fate of music, poetry and literature under these conditions, Adorno advocated a hermetic art of silence and dissonance, as exemplified by Paul Celan and above all Samuel Beckett. This article shows that in the visual arts, too, the genocidal violence of World War II was confronted with analogous strategies of indirection. In Plight, Beuys would successfully synthesize John Cage’s symbolic demolitions of traditional music and the investigations of negative presentation carried out in sculpture by Arman and Daniel Spoerri.